Early surfactant and non-invasive ventilation versus intubation and surfactant: a propensity score-matched national study. Issue 1 (27th July 2022) - Reigstad, Hallvard; Hufthammer, Karl Ove; Rønnestad, Arild E; Klingenberg, Claus; Stensvold, Hans Jørgen; Markestad, Trond
Abstract : Objective: To compare outcome after less invasive surfactant administration (LISA) and primary endotracheal intubation (non-LISA) in infants born before gestational age (GA) 28 weeks. Setting: All neonatal intensive care units (NICUs) in Norway during 2012–2018. Methods: Defined population-based data were prospectively entered into a national registry. We compared LISA infants with all non-LISA infants and with non-LISA infants who received surfactant following intubation. We used propensity score (PS) matching to identify non-LISA infants who were similar regarding potential confounders. Main outcome variables: Rate and duration of mechanical ventilation (MV), survival, neurological and gastrointestinal morbidity, and need of supplemental oxygen or positive pressure respiratory support at postmenstrual age (PMA) 36 and 40 weeks. Results: We restricted analyses to GA 25–27 weeks (n=843, 26% LISA) because LISA was rarely used at lower GAs. There was no significant association between NICUs regarding proportions treated with LISA and proportions receiving MV. In the PS-matched datasets, fewer LISA infants received MV (61% vs 78%, p<0.001), and they had fewer days on MV (mean difference 4.1, 95% CI 0.0 to 8.2 days) and lower mortality at PMA 40 weeks (absolute difference 6%, p=0.06) compared with all the non-LISA infants, but only a lower rate of MV (64% vs 97%, p<0.001) and fewer days on MV (mean difference 5.8, 95% CI 0.6 to 10.9 days) compared with non-LISA infants who received surfactant after intubation. Conclusion: LISA reduced the rate and duration of MV but had no other clear benefits.